Therapeutic targets for lung cancer: genome-wide Mendelian randomization and colocalization analyses - Luan, Yi; Xian, Desheng; Zhao, Changwen; Qing, Xin; He, Hanlin; Zheng, Kaixuan; Song, Wenjun; Jiang, Taijiao; Wang, Wenjian; Duan, Chaohui (Frontiers in Pharmacology, 2024)
Background Lung cancer, categorized into non-small cell lung cancer (NSCLC) and small cell lung cancer (SCLC), remains a significant global health challenge. The development of drug resistance and the heterogeneity of the disease necessitate the identification of novel therapeutic targets to improve patient outcomes. Methods We conducted a genome-wide Mendelian randomization (MR) and colocalization analysis using a comprehensive dataset of 4,302 druggable genes and cis-expressed quantitative trait loci (cis-eQTLs) from 31,884 blood samples. The study integrated genomic analysis with eQTL data to identify key genes associated with lung cancer risk. Results The analysis revealed five actionable therapeutic targets for NSCLC, including LTB4R, LTBP4, MPI, PSMA4, and TCN2. Notably, PSMA4 demonstrated a strong association with both NSCLC and SCLC risks, with odds ratios of 3.168 and 3.183, respectively. Colocalization analysis indicated a shared genetic etiology between these gene expressions and lung cancer risk. Conclusion Our findings contribute to precision medicine by identifying druggable targets that may be exploited for subtype-specific lung cancer therapies.